Muscle Pain Code: a novel tool for screening the risk of time-loss muscle injury in professional male football players - Flores, H. N.; Tamujo, A. C.; Cetolin, T.; Ribeiro-Alvares, J. B.; de Noronha, M.; Baroni, B. M.; Haupenthal, A. (The Physician and Sportsmedicine, 2024)
Objective To investigate the association of a novel post-match muscle pain map, named Muscle Pain Code (MPC), with the risk of subsequent time-loss muscle injury in a cohort of professional football (soccer) players.